Film depictions of emotionally abusive coach–athlete interactions. Issue 1 (2nd January 2016) - Kerr, Gretchen; Stirling, Ashley; Bandealy, Ahad
Abstract: This study examined film portrayals of coach–athlete interactions in 19 popular, North American, sport films, with a focus on emotional abuse within the coach–athlete relationship. Using a confirmatory thematic approach, themes within the films were coded deductively relative to pre-determined categories derived from previous literature on athletes' experiences of emotional abuse in sport. In total, 346 emotionally abusive interactions were observed. Emotionally abusive coaching practices were most frequently used by head coaches in the forms of verbal comments, physically threatening behaviours, and the denial of attention and support against athletes. The majority of the incidents occurred in athletic venues in response to sport-related performance errors and in the presence of bystanders. Recommendations are made to empirically explore the potential of film portrayals to contribute to the normalisation of emotionally abusive coaching practices.